(3YGdejI JLGQI GdbQf GdMGOj hGdYTQjf (B(1) :s (3GdJLGQI GdYGdejI hGdhKjbI GdNJGejI Hjf EfJgGA GdLGJ hbjGe efXeI GdJLGQI GdYGdejI (B/s - (3YHO GdYRjR, SejQ eMeOs ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2006)
(3GdEJaGbjGJ GdYGeI ddJLGQI, GdEJaGbjGJ GdYGeI ddJLGQI aj GdSdY, GdEJaGbjGJ GdYGeI ddJLGQI aj GdNOeGJ, EJaGbjI GdLhGfH GdeJUdI HGdJLGQI aj Mbhb GdedcjI GdacQjI, GdJaGge hJShjI GdefGRYGJ aj EWGQ GdLGJ (B1994(3, hbGFY hCMOGK eG HYO JhbjY GdhKjbI GdNJGejI hbjGe efXeI GdJLGQI GdYGdejIs
Keywords: (3GdJLGQI GdNGQLjIs; (3efXeI GdJLGQI GdYGdejIs